Інформаційна розподілена система підтримки донорів крові - Єсін, К. В. (ХНУРЕ, 2020)
Information distributed system supporting donors is a system that simplifies support for blood donors and recipients. It includes the automatic search for the donor or recipients by the given parameters. The main aim of the work is to implement a system that improves the working process and donor service. The system also helps to create a donor base, which will help in the future with donations.